Perlindungan Hukum terhadap Perawat dalam Pelimpahan Kewenangan Tindakan Medis oleh Dokter di Puskesmas Rawat Inap - Yulia Agustin Suharni; Kusnandar, Mas Iman; Danial Danial (Lembaga Pengembangan Kinerja Dosen, 2026)
The delegation of medical authority from physicians to nurses is a common practice in primary healthcare services, particularly in inpatient public health centers, as a response to limited medical personnel and the demand for continuous healthcare services. However, delegation that is not conducted in accordance with legal provisions may lead to legal uncertainty and increased risks for nurses. This study aims to analyze legal protection for nurses in the delegation of medical authority by physicians in inpatient public health centers. The research employs a normative juridical method using statutory and conceptual approaches through the examination of legal doctrines and principles related to authority, delegation, and mandate. The findings indicate that although the legal framework governing the delegation of medical authority is normatively well established, its implementation remains suboptimal, particularly with regard to written delegation, physician supervision, and legal awareness among healthcare professionals. Verbal delegation practices and unclear boundaries of authority weaken legal protection for nurses and increase the risk of legal liability. This study emphasizes that delegation of medical authority conducted in writing, on a case-by-case basis, based on nurses’ competencies, and under physician supervision is a fundamental prerequisite for ensuring legal certainty, professional protection, and patient safety.